An Approximate Solution of the Time-Fractional Fisher Equation with Small Delay by Residual Power Series Method. (26th September 2018) - Demir, Ali; Bayrak, Mine Aylin; Ozbilge, Ebru
Abstract : An analytical solution of the time-fractional Fisher equation with small delay is established by means of residual the residual power series method (RPSM) where the fractional derivative is taken in the Caputo sense. Taking advantage of small delay, the time-fractional Fisher equation is expanded in powers series of delay term ϵ . By using RPSM analytical solution of time-fractional of Fisher equation is constructed. The final results and graphical consequences illustrate that the proposed method in this study is very efficient, effective, and reliable for the solution of the time-fractional Fisher equation with small delay.